2018
DOI: 10.3390/ijms19103195
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Chloride Exposure Inhibits Brain Acetylcholine Levels, Produces Neurotoxic Signatures, and Diminishes Memory and Motor Activities in Adult Zebrafish

Abstract: In this study, we evaluated the acute (24, 48, 72, and 96 h) and chronic (21 days) adverse effects induced by low doses (0.1, 0.5, 1, and 1.5 mg/L) of zinc chloride (ZnCl2) exposure in adult zebrafish by using behavioral endpoints like three-dimensional (3D) locomotion, passive avoidance, aggression, circadian rhythm, and predator avoidance tests. Also, brain tissues were dissected and subjected to analysis of multiple parameters related to oxidative stress, antioxidant responses, superoxide dismutase (SOD), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 83 publications
2
49
0
Order By: Relevance
“…A biochemical survey demonstrated that the behavioral alterations may be correlated to oxidative stress, lipid peroxidation, and stress (summarized in Figure 10). it was discovered that the AChE activity in the brain of the zebrafish increased after chronic zinc exposure at 0.1 ppm for 21 days [57]. We suggest that the inconsistency of the AChE activity response toward heavy metals may be correlated to the nature of the animal model and exposure dose and duration (short-term or long-term).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…A biochemical survey demonstrated that the behavioral alterations may be correlated to oxidative stress, lipid peroxidation, and stress (summarized in Figure 10). it was discovered that the AChE activity in the brain of the zebrafish increased after chronic zinc exposure at 0.1 ppm for 21 days [57]. We suggest that the inconsistency of the AChE activity response toward heavy metals may be correlated to the nature of the animal model and exposure dose and duration (short-term or long-term).…”
Section: Discussionmentioning
confidence: 81%
“…In another study, the AChE levels in Seriola dumerilli were upregulated after Cd exposure at a dose of 50 µg/kg and downregulated at a dose of 100 and 250 µg/kg [56]. In addition, it was discovered that the AChE activity in the brain of the zebrafish increased after chronic zinc exposure at 0.1 ppm for 21 days [57]. We suggest that the inconsistency of the AChE activity response toward heavy metals may be correlated to the nature of the animal model and exposure dose and duration (short-term or long-term).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a previous study, we discovered that low concentrations of ZnCl 2 could reduce the brain acetylcholine content and induce memory loss in zebrafish by using a passive avoidance shuttle box test [25]. However, in the passive avoidance test, there is a tendency that the zebrafish will swim in the dark area as an innate response (usually less than 5 s).…”
Section: Comparison Of Learning Capacity and Memory Retention Betweenmentioning
confidence: 99%
“…The first group without treatment of ZnCl 2 served as control group. The treatment group was waterborne exposed to 100 ppb ZnCl 2 solution for 96 h according to our previous tested condition [25]. After ZnCl 2 incubation, fish were washed three times with excess water and then transferred into individual tanks for memory testing by using a T-maze.…”
Section: Zncl 2 Exposure Incubationmentioning
confidence: 99%